Extraction Optimization of Polyphenols from Waste Kiwi Fruit Seeds (Actinidia chinensis Planch.) and Evaluation of Its Antioxidant and Anti-Inflammatory Properties - Deng, Jianjun (Molecules, 2016)
Kiwi fruit (Actinidia chinensis Planch.) seeds, present as a by-product in the food and pharmaceutical industries, remain underutilized. In this study the extraction conditions for the maximum recovery of total phenolic content (TPC) with high DPPH scavenging capacities (DPPHsc) were analyzed for kiwi fruit seed polyphenols (KSP) by response surface methodology. The optimal conditions for the highest yield of TPC (53.73 mg GAE/g DW) with 63.25% DPPHsc was found by using an extraction time of 79.65 min with an eluent containing 59.45% acetone at 38.35 °C and a 1:11.52 (w/v) solid/liquid ratio. Compared with butyl hydroxy toluene (BHT), a synthetic antioxidant, the extracted KSP showed higher DPPHsc and ferric reducing antioxidant power, but was less efficient than grape seed polyphenols extracted under the same optimum conditions. We also showed that the extracted KSP exhibited strong anti-inflammatory activities by suppressing the secretion of pro-inflammatory cytokines like interleukin-1β (IL-1β) and tumor necrosis factor-alpha (TNF-α) in lipopolysaccharides (LPS)-induced RAW 264.7 cells. High performance liquid chromatography-electrochemical detector (HPLC-ECD) analysis of the extracted KSP under optimized conditions revealed that the extract was mainly composed of five polyphenolic compounds. Our work showed the development of an optimal extraction process of the KSP, which presented excellent antioxidant and anti-inflammatory activities, indicating that kiwi fruit seeds may further be utilized as a potential source of natural biological active compounds.